2007
DOI: 10.7863/jum.2007.26.11.1461
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to the Use of the Multiplanar Display in Evaluation of Abnormal Vascular Connections to the Fetal Heart Using 4-Dimensional Ultrasonography

Abstract: Objective. The multiplanar display is a modality that allows the simultaneous visualization of 3 orthogonal planes from volume data sets obtained with 3-and 4-dimensional ultrasonography. Simultaneous display of standard views used in fetal echocardiography and their orthogonal planes may provide novel ultrasonographic views for examination of the fetal heart and its vascular connections. This study was designed to determine the clinical utility of the multiplanar display in the examination of abnormal vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…[48] It has also been demonstrated that multiplanar display may help in the evaluation of abnormal vascular connections. [49]…”
Section: Discussionmentioning
confidence: 99%
“…[48] It has also been demonstrated that multiplanar display may help in the evaluation of abnormal vascular connections. [49]…”
Section: Discussionmentioning
confidence: 99%
“…The end result is a multitude of display modes for STIC volume data sets. Congenital Heart Disease —Prenatal assessment and diagnosis of CHD using conventional 2D sonography require an analysis of anatomic structures through a mental reconstruction of their spatial relationships. Four‐dimensional sonography with STIC can improve the ability to identify such complex intracardiac relationships (Figure 9 and Video 13) and may also shorten the examination time 33 , 43 , 121 . Moreover, fetal cardiac abnormalities undetected during real‐time sonographic examination may be detected at the time of STIC volume review 40 .…”
Section: Characteristic Features and Applications Of 4d Sonography Wimentioning
confidence: 99%
“…A solid body of evidence suggests that 4D sonography with STIC facilitates examination of the fetal heart 3 , 4 , 5 , 11 37 and may also be used to evaluate fetal cardiac function 18 , 22 , 27 , 30 , 31 , 33 , 38 46 . This modality has also been used in the prenatal evaluation and diagnosis of congenital heart disease (CHD) 2 , 20 , 47 71 because it improves the ability to identify complex intracardiac relationships and can shorten the examination time 3 , 17 , 72 . These facts are important, since evaluation of the normal and abnormal fetal heart 73 75 using 2D sonography is one of the most challenging tasks in prenatal diagnosis.…”
Section: How To Perform 4d Sonography With Sticmentioning
confidence: 99%